100 kHz, femtosecond, 4-10 μm tunable, AgGaSe2-based OPA pumped by a CPA Tm: Fiber laser system - Baudisch, Matthias; Beutler, Marcus; Gebhardt, Martin; Gaida, Christian; Stutzki, Fabian; Hädrich, Steffen; Herda, Robert; Zach, Armin; Limpert, Jens; Rimke, Ingo (Optics InfoBase Conference Papers, 2017)
We present the first realization of a femtosecond, mid-to-long-infrared tunable OPA driven by a CPA Tm:fiber-laser with 100 kHz repetition rate. The source provides up to 0.75 μJ energy and supports sub-160 fs pulse durations.
CRIS-Team Scopus Importer:2023-04-20